Mini review : Pengolahan kerupuk “Rambak” kulit di Indonesia - Dedes Amertaningtyas (Faculty of Animal Science, Universitas Brawijaya, 2011)
ABSTRACT: Hide a waste product of animal slaughter house is still can be utilized as food in the form of cracker. Cattle, buffalo, rabbit, chicken shank and fish skin can be used of raw materials for cracker production. This process include hide selection, washing, immersing, liming, deliming, boiling, cutting, immersing in sauce, drying and frying. In Indonesia, the skin cracker industriesare consentralised in certain area of west, central and east java provinces where Sumatra skin cracker are popular knows as “ kerupuk jangek”. Although skin cracker have a high protein content, however its quality are low comparedto other meat processed products. The most dominant amino acid in this product is glycine. Some important issues such as it is not recommended for people suffering uric acid, addition of harmfull additives i.e. formalin and borax, containg chrome which originated from hide prosessing industry and unreligion system of slaughtering (is not halal). Key words: waste product, skin animal, rambak cracker.